English Learning Outcomes through Learning Model and Intrapersonal Intelligence in Vocational High Schools - Heni Rochimah; Muhammad Japar; Etin Solihatin; Masduki Ahmad; Wulandari (JEELS (Journal of English Education and Linguistics Studies), 2025)
Globalization and modernization have made English proficiency a key factor in student success. However, Indonesia's performance remains low, ranking 79th out of 113 countries in the EF English Proficiency Index, with only 46% of students in Bekasi Regency meeting the minimum standard in 2021. This study investigates the impact of intrapersonal intelligence and learning models. Project-Based Learning (PjBL) and Discovery Learning (DL)—on English achievement among vocational high school students. Using a 2x2 factorial experimental design, 70 students were assigned to PjBL (experimental) and DL (control) groups, categorized by high (B1) and low (B2) intrapersonal intelligence. Data were analyzed using two-way ANOVA and Tukey tests. Results revealed: (1) PjBL led to significantly better outcomes than DL; (2) a significant interaction existed between learning models and intrapersonal intelligence; (3) students with high intrapersonal intelligence in the PjBL group outperformed their DL counterparts by 13.20 points; (4) students with low intrapersonal intelligence performed better with DL, with a score difference of -3.90. These findings suggest vocational English teachers should apply PjBL for students with strong intrapersonal skills and DL for those with lower levels. Policymakers are urged to incorporate emotional intelligence components into national curriculum development.